Effect of grain size on the adhesive and ploughing friction behaviours of polycrystalline metals in forming process. (October 2016) - Peng, L.F.; Mao, M.Y.; Fu, M.W.; Lai, X.M.
Abstract: Grain size effect on the friction behaviour of polycrystalline metals in metal forming processes has become one of the most critical issues as the interfacial friction is the most dominating factor which affects the surface quality of the metal-deformed products. Although attentions have been paid to the experimental observation of grain size effect on friction coefficient, the understanding is still quite superficial, and robust conclusions are not yet obtained. To have an in-depth understanding of grain size effect, adhesion and ploughing are studied separately using pin-on-disc friction tests in this research. Different roughness and grain sizes of testing samples are designed for the friction pairs in the experiments to realise both the adhesion-dominated and ploughing-dominated frictions. The experimental results show that with the increase of grain size, the friction coefficient increases in adhesive friction and decreases in ploughing friction. Different mechanisms of the grain size effect on adhesive and ploughing frictions are found by theoretical analysis to account for this phenomenon. For adhesive friction, the transformation from elastic deformation to plastic deformation is the main mechanism. While for ploughing friction, the main mechanism is the transformation from intergranular fracture to transgranular fracture. This work advances the understanding of friction behaviours in metal forming processes and further helps the optimisation of the surface quality of the metal-deformed products. Highlights: Grain size effect on the friction behaviours of polycrystalline metal was studied. Opposite effects of grain size on adhesive and ploughing friction behaviours were observed. A modified ploughing friction model based on fracture mechanics was established. The transformation from adhesive friction to ploughing friction was observed.